Statin therapy in patients with cirrhosis. Issue 4 (8th August 2014) - Wright, Andrew P; Adusumalli, Srinath; Corey, Kathleen E
Abstract : Cardiovascular disease is one of the leading causes of death among patients with cirrhosis and following liver transplantation. Although 3-hydroxy-3-methyl-glutaryl-CoA reductase inhibitors ('statins') reduce the risk of cardiovascular events, fears about hepatotoxicity have historically led to underuse in patients with liver disease. In addition, the pharmacokinetics of statins can be significantly altered in cirrhosis, creating challenges with their use in liver disease. However, emerging data from randomised controlled trials and observational studies suggest that statin therapy appears to be safe and effective in patients with chronic liver disease and compensated cirrhosis. The cardiovascular risk benefits as well as the potential pleiotropic benefits of statins warrants strong consideration of use of statin therapy in patients with cirrhosis.